Gene Expression Profiling of Lacrimal Glands Identifies the Ectopic Expression of MHC II on Glandular Cells as a Presymptomatic Feature in a Mouse Model of Primary Sjögren's Syndrome - Yin, Junping; Zheng, Junfeng; Deng, Fengyuan; Zhao, Wenjie; Chen, Yan; Huang, Qiaoniang; Huang, Renliang; Wen, Lifang; Yue, Xiaoyang; Petersen, Frank; Yu, Xinhua (Frontiers in Immunology, 2018)
Ectopic expression of MHC II molecules on glandular cells is a feature of primary Sjögren's syndrome (pSS). However, the cause of this ectopic expression and its potential role in the pathogenesis of the disease remains elusive. Here, we report that ectopic expression of MHC II molecules on glandular cells represents an early presymptomatic event in a mouse model of pSS induced by immunization of Ro60_316-335 peptide emulsified in TiterMax® as an adjuvant. Ectopic expression of MHC II was induced by TiterMax® but not by complete freund's adjuvant (CFA). Furthermore, immunization with Ro60_316-335 peptide emulsified in TiterMax®, but not in CFA, induced a pSS-like disease in mice. Our results suggests that ectopic expression of MHC II molecules on glandular cells represents a presymptomatic feature of pSS and that such ectopic expression can be induced by exogenous factors. In addition, this study also provides a novel mechanism how adjuvants can amplify immune responses.